Memantine Modulates Oxidative Stress in the Rat Brain following Experimental Autoimmune Encephalomyelitis - Beata Dąbrowska-Bouta (MDPI AG, 2021)
Experimental autoimmune encephalomyelitis (EAE) is an animal model most commonly used in research on the pathomechanisms of multiple sclerosis (MS). The inflammatory processes, glutamate excitotoxicity, and oxidative stress have been proposed as determinants accompanying demyelination and neuronal degeneration during the course of MS/EAE. The aim of the current study was to characterize the role of NMDA receptors in the induction of oxidative stress during the course of EAE. The effect of memantine, the uncompetitive NMDA receptor antagonist, on modulation of neurological deficits and oxidative stress in EAE rats was analyzed using several experimental approaches. We demonstrated that the expression of antioxidative enzymes (superoxide dismutases SOD1 and SOD2) were elevated in EAE rat brains. Under the same experimental conditions, we observed alterations in oxidative stress markers such as increased levels of malondialdehyde (MDA) and decreased levels of sulfhydryl (-SH) groups, both protein and non-protein (indicating protein damage), and a decline in reduced glutathione. Importantly, pharmacological inhibition of ionotropic NMDA glutamate receptors by their antagonist memantine improved the physical activity of EAE rats, alleviated neurological deficits such as paralysis of tail and hind limbs, and modulated oxidative stress parameters (MDA, -SH groups, SOD’s). Furthermore, the current therapy aiming to suppress NMDAR-induced oxidative stress was partially effective when NMDAR’s antagonist was administered at an early (asymptomatic) stage of EAE.